Skill Profiles for Employability: (Mis)Understandings between Higher Education Institutions and Employers - Luís Sebastião; Filipa Tirapicos; Rita Payan-Carreira; Hugo Rebelo (MDPI AG, 2023)
There is a consensus that employers, when recruiting, look for future employees to have a certain required profile. This profile consists of a set of skills that are considered crucial for the correct performance of the tasks that the employees will be performing. It is usually easy to identify which hard skills employers require, but it is not so easy to find out which soft skills employees should have. In addition to this difficulty, there is the possibility that higher education institutions may not be preparing students to align with employers' envisioned skill sets. As part of the European Project "Think4Jobs" (2020-1-EL01-KA203-078797), an exploratory study was conducted to understand whether higher education institutions develop, and employers demand, individuals with the same profiles and to characterise these profiles. For this purpose, eight directors of different higher education programmes and six employers were interviewed. The information from the interviews was processed using the content analysis technique with the support of the NVivo data analysis software. The findings indicate that both educators and employers acknowledge the significance of soft skills, assigning them higher importance than hard skills, and the necessity of coordination between the two skill sets. Respondents also emphasised the importance of training, with course directors focusing more on initial training, while employers highlighted in-job training. Motivation, creativity, interpersonal relationships, communication, initiative and critical thinking were the skills identified by both groups as essential to an employee's profile.